Portable chlorophyll meter in monitoring and management of nitrogen in common bean cultivars - Filla, Vinicius Augusto [UNESP]; Coelho, Anderson Prates [UNESP]; Leal, Fabio Tiraboschi [UNESP]; Trombeta Bettiol, Joao Victor [UNESP]; Lemos, Leandro Borges [UNESP] (Univ Nacional Cuyo, Fac Ciencias Agrarias, 2020)
More sustainable practices involving biological nitrogen fixation (BNF) and the use of portable chlorophyll meter in fertilization management are promising to increase nitrogen (N) use efficiency in the common bean crop. This study aimed to monitor N managements using a portable chlorophyll meter and its effects on agronomic attributes of Carioca-type common bean cultivars with indeterminate and determinate growth habits ('IPR Campos Gerais' and 'IAC Imperador'). The experiment was carried out in a randomized block design (RBD), in a 2 x 9 factorial scheme, with four replicates. The first factor consisted of the cultivars and the second factor of the N management. The data were subjected to analysis of variance by F test and, when necessary, the means were grouped by the Scott-Knott test at 5% probability level. The use of portable chlorophyll meter is a viable alternative for N monitoring and management in common bean, allowing the reduction of top-dressing N application, regardless of the cultivar used.
Keywords: Phaseolus vulgaris L.; chlorophyll index; biological nitrogen fixation; agronomic nitrogen efficiency